Peran Guru dalam Mengembangkan Rasa Percaya Diri Anak melalui Kegiatan Bermain Puzzle di Pendidikan Anak Usia Dini Mutiara Bunda Desa Delima Kecamatan Tebing Tinggi - Ummi Khanifah; Husin Husin (Lembaga Yasin AlSys, 2026)
The development of children’s self-confidence through play activities has been widely studied, but the teacher’s role in managing puzzle play activities to foster early childhood self-confidence has not yet been explained in depth. This study aims to analyze teachers’ roles, constraints, and efforts in developing children’s self-confidence through puzzle play activities at PAUD Mutiara Bunda, Delima Village, Tebing Tinggi Subdistrict. This study used a qualitative approach with a descriptive design. The research participants consisted of the principal, one B1 class teacher, and 14 children selected purposively. Data were collected through semi-structured interviews, participatory observation, and documentation, and were then analyzed through the stages of data reduction, data display, and conclusion drawing. The results show that the teacher acts as a facilitator, motivator, guide, role model, and creator of a safe and enjoyable learning atmosphere. The constraints identified include limited media, differences in children’s abilities, and variations in motivation and interest. The teacher’s efforts to overcome these constraints were carried out through providing opportunities for independence, gradual guidance, positive reinforcement, role modeling, and an individual approach. The conclusion of this study emphasizes that the effectiveness of puzzle games in developing children’s self-confidence is determined by the quality of teacher assistance in creating adaptive, supportive, and child-centered learning. These findings provide practical implications for early childhood education institutions to provide more diverse play media and improve teachers’ competence in play-based learning.